2021
DOI: 10.3168/jds.2020-18975
|View full text |Cite
|
Sign up to set email alerts
|

Cell death-inducing DNA fragmentation factor-α-like effector C (CIDEC) regulates acetate- and β-hydroxybutyrate-induced milk fat synthesis by increasing FASN expression in mammary epithelial cells of dairy cows

Abstract: Increasing acetate and β-hydroxybutyrate (BHB) supply to lactating cows will increase milk fat synthesis. However, the underlying molecular mechanism remains largely unknown. Cell death-inducing DNA fragmentation factor-α-like effector C (CIDEC) is a lipid dropletassociated protein that promotes intracellular triacylglycerol accumulation. In the present study, using gene overexpression and knockdown, we detected the contributions of CIDEC on milk fat synthesis in mammary epithelial cells of dairy cows in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Acetate is the main lipogenic substrate in the process of de novo FA production within mammary tissues of dairy cows. 2 As a Gprotein-coupled receptor, GPR43 is related to adipocyte differentiation. 24 Our study demonstrated that GPR43 was highly expressed within mammary tissues in lactating cows and functioned in milk fat production.…”
Section: ■ Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Acetate is the main lipogenic substrate in the process of de novo FA production within mammary tissues of dairy cows. 2 As a Gprotein-coupled receptor, GPR43 is related to adipocyte differentiation. 24 Our study demonstrated that GPR43 was highly expressed within mammary tissues in lactating cows and functioned in milk fat production.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Acetate is the main lipogenic substrate in the process of de novo FA production within mammary tissues of dairy cows . As a G-protein-coupled receptor, GPR43 is related to adipocyte differentiation .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FASN is a key enzyme in the regulation of the de novo synthesis of milk lipids. In BMECs, cell-death-induced DNA fragmentation factor α-like effector C (CIDEC) regulates acetate-induced milk fat synthesis by increasing FASN expression . In buffalo mammary glands, liver X receptor α (LXRα) promotes milk fat synthesis by regulating FASN expression through direct interactions with the FASN promoter .…”
Section: Discussionmentioning
confidence: 99%
“…Mammary tissue samples from 3 lactating cows at 90 DIM were used for mammary epithelial cell isolation. Cells were cultured in DMEM/F12 supplemented with 10% FBS, penicillin (100U/mL), and streptomycin (100μg/mL) as previously described (Lv et al ., 2021).…”
Section: Methodsmentioning
confidence: 99%